For integer k ≥ 0 and prime p find n for which:
q = 1 ∑ p n − k g cd ( q , p n − k ) = p n − k + 1
Notation:
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Elegant solution!
Let's evaluate sum in left part: q = 1 ∑ p n − k gcd ( q , p n − k ) = p n − k + q = 0 ∑ n − k − 1 ( p q p n − k − p q + 1 p n − k ) p q = p n − k + q = 0 ∑ n − k − 1 ( p q p n − k − p n − k − 1 ) p q = = p n − k + q = 0 ∑ n − k − 1 ( p n − k − p n − k − 1 ) = p n − k + ( n − k ) ( p n − k − p n − k − 1 ) , n ≥ k ; n ≥ k because gcd ( ⋅ ) : Z → N and if n < k then p n − k non-integer. Solve the equation: p n − k + ( n − k ) ( p n − k − p n − k − 1 ) = p n − k + 1 ; ( n − k ) ( p n − k − p n − k − 1 ) = p n − k + 1 − p n − k ; ( n − k ) ( p n − k − p n − k − 1 ) = p ( p n − k − p n − k − 1 ) ; p n − k − p n − k − 1 > 0 , because p > 1 , so we can divide the two parts of the equation: n − k = p ⇒ n = p + k > k
Problem Loading...
Note Loading...
Set Loading...
For this, it is instructive to use the Euler Totient Function and we'll also put m = n − k . We can dive the summation into two parts, one that p ∣ q , in which we'll write q = p q 1 , and another part in which this doesn't happen, so the gcd is 1. Concretely, since there are ϕ ( p m ) terms on the latter term:
∑ q = 1 p m g c d ( q , p m ) = ∑ q 1 = 1 p m − 1 g c d ( p q 1 , p m ) + ϕ ( p m ) = p ∑ q 1 = 1 p m − 1 g c d ( q 1 , p m − 1 ) + ϕ ( p m )
Now we can use induction on the sum factor to show:
∑ q = 1 p m g c d ( q , p m ) = p m + ∑ j = 1 m p m − j ϕ ( p j )
So now, we use the fact that ϕ ( p j ) = p j − p j − 1 :
∑ q = 1 p m g c d ( q , p m ) = p m + ∑ j = 1 m p m − j ( p j − p j − 1 ) = p m + ∑ j = 1 m ( p m − p m − 1 ) = p m + m ( p m − p m − 1 )
Back to the question, we want p m + 1 = ∑ q = 1 p m g c d ( q , p m ) = p m + m ( p m − p m − 1 ) → m ( p m − p m − 1 ) = p m + 1 − p m → m = p . Therefore, n = p + k